Comparing the body mass index, blood pressure and blood biochemical changes during Ramadan between high to moderate level and low level physical activity groups prior to Ramadan among overweight and obese working women - Ismail, Suriani; Shamsuddin, Khadijah; Abdul Latif, Khalib; Abu Saad, Hazizi (Medip Academy, 2016)
Background: Physical inactivity and sedentary lifestyle are among the most certain causes of overweight and obesity and vice versa, increased physical activity is among the most certain means to reduce body weight in most overweight and obese cases. The objective of the study was to compare the blood pressure, blood lipid profile (i.e. total cholesterol (TC), high density lipoprotein (HDL-C), low density lipoprotein (LDL-C)) and triglyceride (TG) and fasting blood sugar (FBS) changes during Ramadan between those with ‘high to moderate level’ of physical activity and those with ‘low physical activity’ before Ramadan.